The Effect of Brand Positioning and Service Quality on Customer Loyalty in Wonoayu Eurocar Market With Customer Satisfaction As Moderation Variable - Muhammad Yosa Vernanda; Dewi Komala Sari (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to determine the effect of brand positioning on customer loyalty, to determine service quality on customer loyalty, to determine customer satisfaction that moderates the influence of brand positioning and service quality on customer loyalty in the Eurocar Market in Wonoayu. This research is quantitative research with hypothesis testing. The sample collection method uses non probability sampling and 115 respondents are obtained using incidental sampling techniques. The analytical tool used is Structural Equation Modeling and moderation regression with the AMOS 21 program. The results of this study prove that there is a significant influence of brand positioning variables on customer loyalty, related to significant variables of service quality on customer loyalty, customer satisfaction variables moderate the influence of brand positioning on loyalty customers, customer satisfaction moderates the orientation of service quality towards customer loyalty.